Analysis of Student Needs for the Development of Sepak Takraw Teaching Materials to Improve Learning Outcomes in Elementary Schools - Tamrin, Muhammad; Iksan, Andi; Ajju, Juhannis (Indonesian Journal Publisher, 2025)
This study aims to analyze the needs of elementary school students for the development of effective sepak takraw teaching materials to enhance learning outcomes in physical education. Utilizing a descriptive survey methodology, data were collected through questionnaires distributed to both students and physical education teachers in several elementary schools. The findings indicate that students require interactive, accessible, and age-appropriate sepak takraw materials tailored to their cognitive and physical development. Additionally, challenges such as limited teaching resources and a lack of varied learning media were identified. The results highlight the importance of designing sepak takraw instructional materials based on student needs to increase motivation and improve academic performance in elementary physical education